More souls to feed: the population impact on prices in late colonial Alto Peru and Buenos Aires - Agustina Vence Conti; Eduardo Martin Cuesta (Cambios y Permanencias, 2019)
The aim of this paper is to trace and analyze the price behavior during the eighteenth century in two regions of the Spanish Empire: Alto Peru and Buenos Aires. These two zones had a divergent economic performance; while one of them showed an economic take-off the other became stagnant.